(untitled) (Journal of Medical & Health Sciences Review, 2025)
Air pollution and climate change are two of the most pressing environmental challenges of the 21st century, posing a combined threat to both natural ecosystems and human health. While often studied separately, these issues are deeply interconnected, sharing common sources and amplifying each other’s effects. This paper explores the dual impact of air pollution and climate change, emphasizing their synergistic nature and the resulting consequences on ecological stability and public health. Anthropogenic activities such as fossil fuel combustion, industrial emissions, and deforestation contribute significantly to the release of air pollutants (e.g., particulate matter, nitrogen oxides, sulfur dioxide) and greenhouse gases (e.g., carbon dioxide, methane). These pollutants not only disrupt atmospheric composition but also lead to acid rain, ocean acidification, soil degradation, and biodiversity loss. Simultaneously, climate change exacerbates air quality problems through increased frequency of wildfires, heatwaves, and stagnant air masses. The human health implications include a rise in respiratory and cardiovascular diseases, premature deaths, and heightened vulnerability among children, the elderly, and low-income communities. This paper also discusses the socioeconomic dimensions of the crisis and highlights current mitigation and adaptation strategies, including clean energy technologies, policy frameworks, and community-based actions. By examining the interplay between air pollution and climate change, this research underscores the need for integrated, interdisciplinary approaches to achieve sustainable environmental and health outcomes. Coordinated global efforts are essential to curb emissions, enhance resilience, and safeguard both ecological integrity and human well-being.